Review of Freedom of Religion or Belief (KBB) in the Implementation of the Inter-Religious Education Model at the Defense University - Sulaiman (ENDLESS: INTERNATIONAL JOURNAL OF FUTURE STUDIES, 2022)
After the reform era, Indonesia was once known as a tolerant country that was able to combine religion and democracy. However, in the last five years, this image has begun to be doubted in line with the increasing complexity of diversity and the conflicts that have arisen. Indonesia adopts a mono-religious approach in the setting of religious education, but some institutions adopt an inter-religious model. This article compares views on freedom of religion or belief (KBB) with the management of the Religious Education course at the Defense University, which applies an inter-religious model in the Buddhist Religious Education sub-course. The Review on Freedom of Religion or Belief (KBB) in this study sees that this innovation provides new insights and solutions to overcome the challenges faced in the implementation and sustainability of inter-religious education programs. The Defense University can ensure that the inter-religious education programs they run remain effective and sustainable in creating an environment that is inclusive and respects freedom of religion or belief. It is hoped that through this effort, a new generation of leaders who respect diversity and are able to uphold the values of tolerance, harmony and freedom of religion or belief will continue to be born and develop, for the progress and prosperity of the Indonesian nation.